2022
DOI: 10.3390/biology11020193
|View full text |Cite
|
Sign up to set email alerts
|

Crop Wild Relatives (CWRs) Threatened and Endemic to Italy: Urgent Actions for Protection and Use

Abstract: An updated overview of the 29 threatened crop wild relatives (CWRs) endemic to Italy is presented, namely: Arrhenatherum elatius subsp. nebrodense, Barbarea rupicola, Brassica baldensis, Brassica glabrescens, Brassica macrocarpa, Brassica rupestris subsp. hispida, Brassica rupestris subsp. rupestris, Brassica tardarae, Brassicatrichocarpa, Brassica tyrrhena, Brassica villosa subsp. bivonana, Brassica villosa subsp. brevisiliqua, Brassica villosa subsp. drepanensis, Brassica villosa subsp. tineoi, Brassica vill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 124 publications
0
29
0
Order By: Relevance
“…Assuming that key environmental factors for grape berry and wine quality—such as temperature—are predicted to vary in the next decades due to climate change [ 27 ], it is important to examine the natural plasticity of different cultivars to the predicted thermal increase. Phenotypic plasticity (or adaptability), defined as the ability of an organism (wild and cultivated) to change its phenotype in response to different environments, can help mitigate negative effects due to environmental perturbations [ 28 , 29 ]. For Mendoza region, a 2–4 °C increase in the mean diurnal temperature during summer has been predicted for the end of this century [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that key environmental factors for grape berry and wine quality—such as temperature—are predicted to vary in the next decades due to climate change [ 27 ], it is important to examine the natural plasticity of different cultivars to the predicted thermal increase. Phenotypic plasticity (or adaptability), defined as the ability of an organism (wild and cultivated) to change its phenotype in response to different environments, can help mitigate negative effects due to environmental perturbations [ 28 , 29 ]. For Mendoza region, a 2–4 °C increase in the mean diurnal temperature during summer has been predicted for the end of this century [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the identification of some AGPs lacking signal peptides in Arabidopsis, wheat ( Triticum aestivum L.), and rice and some AGPs potentially lacking well-identified O -glycosylation sites in poplar ( Populus trichocarpa Torrey & A. Gray ex Hooker), Chinese cabbage, wheat, and rice through bioinformatics approaches is challenging our conventional concept to define an AGP [ 7 , 35 , 44 , 45 , 46 ], without excluding that there are several wild species, including crop wild relatives, of which we have no data, not only for AGPs, but even for their chemical composition [ 47 , 48 , 49 ].…”
Section: Characteristics Classification and Identification Of Agpsmentioning
confidence: 99%
“…Starting from the crop wild relatives (CWR), including those belonging to the genus Aegilops, from which humans began to select the different species of wheat cultivated today [ 32 , 33 , 34 ], this study identified drought memory response miRNAs and their target genes in wheat by small RNA and degradome sequencing and further analyzed the biological functions of candidate miRNAs. Our results provide insight into wheat drought memory and its possible molecular mechanisms and would be of great significance in breeding new drought-resistant wheat varieties.…”
Section: Introductionmentioning
confidence: 99%